Intraday patterns of liquidity on the Warsaw stock exchange before and after the outbreak of the COVID-19 pandemic - Jakub Kubiczek; Marcin Tuszkiewicz (International Journal of Financial Studies, 2022)
A highly significant feature of the stock market is its efficiency, which is associated with information efficiency. However, the liquidity of stock on the market is its essential characteristic. The inflow of information in highly liquid markets allows for the maintenance of high information efficiency. The COVID-19 pandemic affected many aspects related to stock markets, including their liquidity. The impact of the pandemic is so multidimensional that there are still areas that need to be investigated. One of them is the intraday liquidity patterns on the stock markets. Therefore, the present paper aims to verify the existence of intraday liquidity patterns on the Warsaw Stock Exchange in three periods: before, during and after the panic caused by the first wave of the COVID-19 pandemic. The results confirmed the existence of a U-shaped intraday distribution of the number of transactions and their trading. This outcome highlights the importance of the first and last minutes of a trading session. The COVID-19 pandemic resulted in the domination of WSE transactions of small individual investors who feared the loss of value of their assets, selling them on the stock exchange. In the pandemic, the average percentage change between transactions increased.
Keywords: 330; COVID-19 pandemic; intraday patterns; investors' behaviors; liquidity; stock market; Warsaw Stock Exchange